Salesperson brand attachment: a job demands-resources theory perspective. Issue 1 (2nd January 2016) - Allison, Lee; Flaherty, Karen E.; Jung, Jin Ho; Washburn, Isaac
Abstract : Sales researchers have largely ignored the idea that salespeople form attachments to the brands that they sell, and that these attachments hold important consequences for sales outcomes. Drawing on job demands-resources theory, the authors suggest that salesperson brand attachment (SBA) serves as a unique psychological resource for salespeople. Using data from 154 salespeople from the beverage industry, they provide evidence that SBA increases selling effort toward the brand, and ultimately job satisfaction. In addition, they show that salesperson's brand attachment acts as a buffer against perceived job demands, including job codification and hierarchy of authority. In general, results support the job demands-resources framework and confirm that SBA is a resource that may be leveraged to offset job demands, under certain situations.